2018
DOI: 10.1021/acs.energyfuels.7b03457
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Crystallization of Aqueous Droplets in Water-in-Crude Oil Emulsions at Low Temperatures

Abstract: This study focused on the examination of the isothermal crystallization of aqueous droplets in water-in-crude oil emulsions with water concentrations in the range of 5 to 20 wt %. Experiments were carried out using differential scanning calorimetry (DSC) with temperatures ranging from −36 °C to −41 °C. The experimental results were approximated using a mathematical kinetic model including the effect of self-acceleration. The rate of crystallization increases with decreasing temperature, and the final accepted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The drop size strongly affects the stability of the emulsion [33] against coalescence. In our previous works [34,35] the influence of droplet size and aqueous phase content on stability of water-in-crude oil emulsions (ϕ = 1-40%), which are the research objects of this work, has been studied by optical microscopy, NMR and Differential Scanning Calorimetry (DSC) techniques. It is found that the droplet size distribution and the mean droplet size can influence the emulsion stability.…”
Section: Rheological Properties Of W/o Emulsionsmentioning
confidence: 99%
“…The drop size strongly affects the stability of the emulsion [33] against coalescence. In our previous works [34,35] the influence of droplet size and aqueous phase content on stability of water-in-crude oil emulsions (ϕ = 1-40%), which are the research objects of this work, has been studied by optical microscopy, NMR and Differential Scanning Calorimetry (DSC) techniques. It is found that the droplet size distribution and the mean droplet size can influence the emulsion stability.…”
Section: Rheological Properties Of W/o Emulsionsmentioning
confidence: 99%
“…The W/O emulsions appear spontaneously, for instance, during offshore petroleum production. Emulsions of this type with brine as a dispersed phase are widely highlighted in the literature. The formation of W/O emulsions leads to high viscosity which makes the transportation of these unconventional oil resources challenging. …”
Section: Introductionmentioning
confidence: 99%
“…Various factors affect emulsion stability/instability. These factors include: Water/oil properties Droplet size of surface active agents: the surface area per unit of mass, as well as the surfactant adsorption on particles, increases as droplet size decreases Stirring rate and/or shear stress exerted; more energy should be exerted to form smaller droplets The percentage of oil and water in emulsion The type and amount of emulsifiers Free energy: spontaneous emulsification may occur if free energy value is negative Temperature: an increase in temperature facilitates emulsion breaking and results in instability of the surface film of the oil-in-water (o/w) emulsion, as a result of reduction in viscosity …”
Section: Introductionmentioning
confidence: 99%
“…Temperature: an increase in temperature facilitates emulsion breaking and results in instability of the surface film of the oil-in-water (o/w) emulsion, as a result of reduction in viscosity …”
Section: Introductionmentioning
confidence: 99%